Gig Economy Management: Managing Flexible Workforce in Digital Ecosystems - Nada Cantika Putri Kadua (PT. Anagata Sembagi Education, 2026)
The rapid expansion of the gig economy has transformed labor dynamics by integrating flexible workers into digital platforms, yet this flexibility is often accompanied by algorithmic control, job insecurity, and limited social protection. This study aims to analyze how gig economy management and flexible workforce strategies can function as core elements within a sustainable digital ecosystem. The research adopts a qualitative approach using a systematic literature review and document analysis of recent peer-reviewed studies and policy reports. Data were analyzed through thematic and qualitative content analysis to identify key patterns related to algorithmic management, workforce flexibility, HRM strategies, and regulatory frameworks. The findings reveal that platform-based labor is characterized by strong algorithmic control over time, space, and performance, which limits worker autonomy while enhancing operational efficiency. Furthermore, the study highlights the need for adaptive and human-centered HRM practices, blended workforce models, and inclusive policy reforms to address labor vulnerabilities. The discussion emphasizes that sustainability in the gig economy depends on balancing technological innovation with worker protection and equity. In conclusion, the integration of ethical algorithmic systems, transparent HRM, and supportive regulations is essential to create a more inclusive and sustainable digital labor ecosystem